Foreign national prisoners in Flanders (Belgium): motivations and barriers to participation in prison programmes - Croux, Flore (European journal on criminal policy and research, 2019)
This exploratory study examines the experiences of foreign national prisoners and the motivations and barriers to their participation in prison programmes (e.g. educational courses, use of the prison library, prison work, sociocultural activities, sports). Data are derived from 15 individual interviews with foreign national prisoners in two Belgian prisons. During the interviews the strengths-based approach of Appreciative Inquiry was used. The results demonstrate that foreign national prisoners experience motivations and barriers that can be placed at the different levels of the ecological model of Bronfenbrenner (1979) which affect individual behaviour: micro-, meso-, exo- and macro-level. Foreign national prisoners were often motivated to participate in prison programmes to improve their health (micro-level) or to facilitate contact inside and outside prison (meso-level). The reverse was also possible; foreign national prisoners were limited in their participation in prison programmes by their social networks (meso-level) and a lack of knowledge and understanding of the available activities (exo-level). In conclusion, limitations, guidelines for further research and implications for practice and policy are considered.